Production of laccase and manganese peroxidase by Pleurotus pulmonarius in solid-state cultures and application in dye decolorization - dos Santos Bazanella, Gisele Cristina; de Souza, Daniela Farani; Castoldi, Rafael; Oliveira, Roselene Ferreira; Bracht, Adelar; Peralta, Rosane Marina (Folia microbiologica, 2013)
The production of ligninolytic enzymes (laccase and Mn-dependent peroxidase) by the white-rot fungus Pleurotus pulmonarius (FR.) Quélet was studied in solid-state cultures using agricultural and food wastes as substrate. The highest activities of laccase were found in wheat bran (2,860 ± 250 U/L), pineapple peel (2,450 ± 230 U/L), and orange bagasse (2,100 ± 270 U/L) cultures, all of them at an initial moisture level of 85 %. The highest activities of Mn peroxidase were obtained in pineapple peel cultures (2,200 ± 205 U/L) at an initial moisture level of 75 %. In general, the condition of high initial moisture level (80-90 %) was the best condition for laccase activity, while the best condition for Mn peroxidase activity was cultivation at low initial moisture (50-70 %). Cultures containing high Mn peroxidase activities were more efficient in the decolorization of the industrial dyes remazol brilliant blue R (RBBR), Congo red, methylene blue, and ethyl violet than those containing high laccase activity. Also, crude enzymatic extracts with high Mn peroxidase activity were more efficient in the in vitro decolorization of methylene blue, ethyl violet, and Congo red. The dye RBBR was efficiently decolorized by both crude extracts, rich in Mn peroxidase activity or rich in laccase activity.
Keywords: Laccase; kultivační média; biotransformace; Coloring Agents; Agriculture; Culture Media; Peroxidases; Biotransformation; průmyslový odpad; lakasa; peroxidasy; zemědělství; Pleurotus; barvicí látky; Industrial Waste